Výstavní pavilon - Zogata, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2013)
V bakalářské práci je vypracován návrh nosné ocelové konstrukce výstavního pavilonu o půdorysných rozměrech 30x36 m, maximální výškou 12 m, pro oblast Brno. Ve statickém výpočtu jsou navrženy a posouzeny hlavní nosné konstrukční prvky jako plnostěnná vaznice, příhradový vazník, ztužidla a plnostěnné sloupy, které spolu s vazníkem tvoří příčnou vazbu, dále patka a kotvení. Součástí práce je výkresová dokumentace skládající se z dispozičního výkresu, příčných řezů, výrobního výkresu vazníku a vybraných detailů.

The goal of this bachelor thesis is to design load bearing steel structure of an exhibition pavilion. The ground plan dimensions are 30 to 36 metres and construction height is 12 metres. The construction is designed for the district of Brno city. There are the following main load bearing structural elements designed and examined in the structural analysis: the solid purlin, panel grider, sway frame, sway bracing and the cross link created by solid columns along with panel girder and column base. The thesis includes documentation composed of layout drawing, cross section, drawing of production and drawing of selected details.
Exhibition pavilion
Keywords: Nosná ocelová konstrukce; výstavní pavilon; vaznice; vazník; příhradový; sloup; ztužidlo; příčná vazba; patka; zatížení; vnitřní síly; posouzení; Load bearing steel structure; exhibition pavilion; purlin; panel girder; column; brace; cross link; column base; load; internal forces; examination.